An Application of Weakly Generalized Closed Graphs - D. Sheeba; N. Nagaveni (International Journal of Mathematics And its Applications, 2017)
We defined some new spaces called as WG-Compact and WG-Connected spaces in order to characterize these spaces by using the notion of weakly generalized closed graphs. And, we investigate the interrelationship among various graph conditions.